Sex- and Gender-Specific Research Priorities for the Emergency Management of Heart Failure and Acute Arrhythmia: Proceedings from the 2014 AEM Consensus Conference Cardiovascular Research Workgroup - McGregor, Alyson J. (Acad Emerg Med, 2014)
The emergency department (ED) is the point of first contact for patients with acute heart failure and arrhythmias, with one million annual ED visits in the United States. Although the total numbers of men and women living with heart failure are similar, female patients are underrepresented in clinical studies, with current knowledge predominantly based on data from male patients. This has led to an under-appreciation of the sex-specific differences in clinical characteristics and pathophysiology-based management of heart failure. Similar disparities have been found in management of acute arrhythmias, especially atrial arrhythmias that lead to an increased risk of stroke in women. Additionally, peripartum and postpartum cardiomyopathy represent a diagnostic and treatment dilemma. This article is the result of a breakout session in the cardiovascular and resuscitation work group of the 2014 Academic Emergency Medicine consensus conference “Gender-Specific Research in Emergency Medicine: Investigate, Understand, and Translate How Gender Affects Patient Outcomes.” A nominal group technique was used to identify and prioritize themes and research questions using electronic mail, monthly conference calls, in-person meetings, and web-based surveys between June 2013 and May 2014. Consensus was achieved through three rounds of nomination followed by the meeting on May 13, 2014, and resulted in seven priority themes that are essential to the common complex clinical syndrome of heart failure for both men and women, and include the areas of pathophysiology, presentation and symptomatology, diagnostic strategies using biomarkers, treatment, and mortality, with special consideration to arrhythmia management and pregnancy.